2018
DOI: 10.1016/j.psychres.2017.09.089
|View full text |Cite
|
Sign up to set email alerts
|

The Beliefs about Voices Questionnaire – Revised: A factor structure from 450 participants

Abstract: Hallucinated voices are common across psychiatric and non-clinical groups. The predominant cognitive theory about the impact of voices posits that beliefs about voice power (‘Omnipotence’) and voice intent (‘Malevolence’/‘Benevolence’) play a key role in determining emotional and behavioral reactions. The revised Beliefs about Voices Questionnaire (BAVQ-R) was designed to assess these constructs, together with two styles of responding (Engagement and Resistance). The BAVQ-R is widely used in clinical and resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 33 publications
(52 reference statements)
0
22
0
4
Order By: Relevance
“…Details about correlations between BAVQ-R and VPD are shown in Table 2. Finally, calculations based on the 4 BAVQ-R factors recently identified by Strauss et al [39] showed the following results: The factor Persecutory Beliefs correlated positively PLOS ONE with Power (r = 0.313, p = 0.002) and Strength (r = 0.228, p = 0.024). The factor Benevolence correlated negatively with Strength (r = -0.249 p = 0.012), Ability to inflict harm (r = -0.339, p = 0.001) and Superiority (r = -0.226, p = 0.025).…”
Section: Construct Validitymentioning
confidence: 81%
“…Details about correlations between BAVQ-R and VPD are shown in Table 2. Finally, calculations based on the 4 BAVQ-R factors recently identified by Strauss et al [39] showed the following results: The factor Persecutory Beliefs correlated positively PLOS ONE with Power (r = 0.313, p = 0.002) and Strength (r = 0.228, p = 0.024). The factor Benevolence correlated negatively with Strength (r = -0.249 p = 0.012), Ability to inflict harm (r = -0.339, p = 0.001) and Superiority (r = -0.226, p = 0.025).…”
Section: Construct Validitymentioning
confidence: 81%
“…Patients’ beliefs about their voices as well as the manner they cope with them were measured with the Beliefs About Voices Questionnaire-Revised (BAVQ-R) [ 57 ]. The BAVQ-R supports four subscales [ 58 ]: two subscales relating to beliefs (persecutory beliefs and benevolence) in addition to two further subscales that measure responses to the voices (resistance and engagement). Depressive symptoms were assessed with the Beck Depression Inventory-II (BDI-II) [ 59 ], which consists of a 21-item self-report inventory.…”
Section: Methodsmentioning
confidence: 99%
“…As suggested by a reviewer, we repeated the mediation analyses using "persecutory beliefs" combining the malevolence and omnipotence subscales, in accordance with the recently proposed BAVQ-R factor structure by Strauss et al [49]. The results remained unchanged; neither the indirect effect from the BCSS negative self via persecutory beliefs on depression (B = 0.07, SE = 0.10; 95% CI -0.14 to 0.28, ab cs = 0.07; 95% CI -0.14 to 0.29), nor the indirect effect from the BCSS negative other via persecutory beliefs on depression (B = 0.12, SE = 0.09; 95% CI -0.01 to 0.34, ab cs = 0.11; 95% CI -0.01 to 0.29) was statistically significant.…”
Section: Relationship Between Interpersonal Schemata Negative Appraimentioning
confidence: 99%